2011
DOI: 10.1002/jcb.23131
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract induced rat pulmonary artery smooth muscle cells proliferation via PKCα-mediated cyclin D1 expression

Abstract: Cigarette smoke could induce pulmonary smooth muscle cells (PASMCs) proliferation. Although our previous study had implied the involvement of protein kinase Cα (PKCα), the molecular mechanism underlying PKCα pathway in this process is still unknown. In this study, rat PASMCs were stimulated by cigarette smoke extract (CSE) or PMA (a special activator to PKCα). Two percent CSE and PMA significantly enhanced cyclin D1 expression and cells proliferation. But cyclin D1-specific siRNA successfully inhibited DNA syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Low concentrations of CSE (1, 2 and 5%) increased cell proliferation, while high concentrations exhibited a significant inhibition on cell proliferation. These results were in accordance with previous studies (34)(35)(36).…”
Section: Discussionsupporting
confidence: 94%
“…Low concentrations of CSE (1, 2 and 5%) increased cell proliferation, while high concentrations exhibited a significant inhibition on cell proliferation. These results were in accordance with previous studies (34)(35)(36).…”
Section: Discussionsupporting
confidence: 94%
“…It has been demonstrated that intervention with anisodamine, an antagonist of muscarinic acetylcholine receptors, via increasing the expression of cyclin D1, prevents smoking-induced ASMC proliferation, exerting a protective and reversing effect regarding CSE-induced changes (27,28). It has been suggested that inhibition of four and a half LIM domains protein 1 limited the CSE-induced proliferation of pulmonary arterial SMCs and may represent a potential therapeutic target for pulmonary hypertension (19).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, brief SHS exposure also has been shown to induce intimal smooth muscle cell proliferation, 98 promote early low-density lipoprotein oxidation, [99][100][101] and even may enhance monocyte adhesion to vascular endothelium. [102][103][104] These mechanisms, in addition to depressed endothelial cell progenitor activity and the resultant dysfunctional vascular repair also seen, 105 create a microenvironment conducive to enhanced atherosclerotic plaque formation.…”
Section: The Physiological Effects Of Shsmentioning
confidence: 99%